Pengaruh Perbandingan Tepung Ketan Putih dan Puree Labu Kuning (Cucurbita moschata D.) Terhadap Karakteristik Mochi - Tika Martina Br Sinaga; Gusti Ayu Kadek Diah Puspawati; Putu Julyantika Nica Dewi (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Mochi is a traditional Japanese cake that has a soft and chewy texture, usually made from white glutinous rice flour, shaped into balls but has a cloudy white color resulting from the glutinous rice flour itself. The nutritional content of mochi is mostly non-fiber carbohydrates. The addition of pumpkin puree has the potential to increase the nutritional value and color of mochi. This study was conducted to determine how the ratio of white glutinous rice flour and pumpkin puree affects the characteristics of mochi and to obtain the right combination to produce mochi with the best characteristics. This study was a laboratory study using a completely randomized design (CRD) with treatments comparing white glutinous rice flour and pumpkin puree consisting of 6 treatment levels, namely: (100%; 0%), (95%;5%), (90%;10%), (85%;15%), (80%;20%), and (75%;25%), with three replicates. The data were analyzed using analysis of variance, and if the treatment was significant (p˂0.05), it was further tested using Duncan's Multiple Range Test (DMRT). The results showed that the ratio of glutinous rice flour and yellow pumpkin puree affected the moisture content, ash, protein, fat, carbohydrates, crude fiber, β-carotene, antioxidant activity, color intensity L*, a*, b*, color preference, aroma, taste, and overall acceptance. The best results were obtained in treatment P5 (75% white glutinous rice flour: 25% yellow pumpkin puree), which produced the best mochi characteristics, including moisture content of 39.50%, ash content of 0.27%, protein content of 4.3%, fat content of 0.91%, carbohydrate content of 54.99%, crude fiber content of 0.15%, β-carotene of 19.36 mg/100g, antioxidant activity of 21.68%, L* value of 48.33; a* value of 17.00; b* value of 60, orange gold color, with a level of preference that was still acceptable to the panelists